Introducing paediatric grommet "rapid turnover" lists. A Quality Improvement Project. Issue 1 (27th April 2016) - Easto, Rachel; Shukla, Rishi; Rowland, Charlie; Williams, Richard
Abstract : Paediatric grommet insertions are a common ENT procedure which is typically carried out as a daycase procedure. National guidelines exist (NICE CG60) outlining the criteria for grommet insertions. At our institution it was noted that children were experiencing long waits for their grommet surgery with 78% breaching the national 18 week RTT target by time of surgery in the preceding 6 months. 38% of children were attending for surgery with out of date audiograms and as a consequence, due to children no longer meeting the NICE criteria for grommet insertions, 8% of children were being cancelled on the day of surgery. To improve our waiting times and reduce on the day cancellations we introduced a pilot scheme of "rapid turnover" paediatric day case theatre lists. These lists were accompanied by a pre-operative consent clinic, enabling children not requiring surgery to be cancelled. The theatre lists were run by a senior ENT registrar and had two anaesthetic "pods" i.e. two anaesthetists and two ODPs. This enabled faster turnover of patients and consequently more patients could be operated on per theatre list. Following our pilot there are no longer any children on the grommet waiting list in breach of the 18 week RTT time. Furthermore, there were no on the day cancellations due to surgery not being indicated. All staff and patients involved were satisfied with the "rapid turnover" lists and subsequently the idea is to be introduced on a regular, 2 monthly basis, to keep waiting times down.